Bladder Oxidative Stress and HMGB1 Release Contribute to PAR4-Mediated Bladder Pain in Mice - Ye, Shaojing; Ma, Fei; Mahmood, Dlovan F. D.; Meyer-Siegler, Katherine L.; Leng, Lin; Bucala, Richard; Vera, Pedro L. (Frontiers in Systems Neuroscience, 2022)
Activation of intravesical PAR4 receptors leads to bladder hyperalgesia (BHA) through release of urothelial macrophage migration inhibitory factor (MIF) and urothelial high mobility group box-1 (HMGB1). MIF deficiency and/or MIF antagonism at the bladder block BHA in mice yet the mechanisms are not clear. Since oxidative stress and ERK phosphorylation are involved in MIF signaling we hypothesized that oxidative stress and/or ERK signaling, activated by MIF release, promote intravesical HMGB1 release to induce BHA. We induced BHA by intravesical PAR4 infusion in female C57BL/6 mice. Mechanical sensitivity was evaluated by measuring abdominal von Frey (VF) 50% thresholds before (baseline) and 24 hr post-infusion. Intravesical pre-treatment (10 min infusion prior to PAR4) with N-acetylcysteine amide (NACA; reactive-oxygen species scavenger; 3 mg in 50 $μ$l), FR180204 (selective ERK1/2 inhibitor; 200 $μ$g in 50 $μ$l), ethyl pyruvate (EP; HMGB1 release inhibitor; 600 $μ$g in 50 $μ$l), or diluent controls (50 $μ$l) tested the effects of pre-treatment on PAR4-induced BHA. Intravesical fluid was collected after each treatment and HMGB1 concentration was measured using ELISA. Awake micturition parameters (volume and frequency) were assessed at the end of the experiments. Bladders were collected and examined for histological signs of edema and inflammation. Pre-treatment with PBS followed by PAR4 induced BHA in mice but PBS followed by scrambled peptide did not. Pre-treatment with NACA or EP partially blocked PAR4-induced BHA while FR180204 had no effect. A significant correlation between intravesical HMGB1 levels and 50% VF thresholds was observed. All PAR4 treated groups had increased levels of HMGB1 in the intravesical fluid compared to PBS-Scrambled group although not statistically significant. No significant effects were noted on awake micturition volume, micturition frequency or histological evidence of bladder edema or inflammation. Our results show that intravesical antagonism of bladder reactive-oxygen species accumulation was effective in reducing PAR4-induced bladder pain. The correlation between intravesical levels of HMGB1 and bladder pain indicates that released HMGB1 is pivotal to bladder pain. Thus, modulating events in the MIF signaling cascade triggered by PAR4 activation (including bladder oxidative stress and HMGB1 release) warrant further investigation as possible therapeutic strategies.